2019
DOI: 10.1002/tox.22775
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of damage by trace amounts of acetamiprid to the midgut of the silkworm, Bombyx mori

Abstract: Acetamiprid is widely used for agricultural pest control. However, it remains poorly understood whether the environmental residues of acetamiprid have the potential effects on economic insect. In this study, we evaluated the effects of acetamiprid on silkworm growth and development. The exposure to trace amounts of acetamiprid significantly decreased body weight, viability, and spinning ability. In addition, the activity of trypsin in the midgut was decreased after exposure. DGE and KEGG pathway enrichment ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Lipase can decompose triglycerides into fatty acids and glycerol. In this study, we found that the activity of lipase was increased at 24 h, which is likely related to the oxidative damage in the midgut caused by glyphosate exposure and is consistent with previously reported results (Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lipase can decompose triglycerides into fatty acids and glycerol. In this study, we found that the activity of lipase was increased at 24 h, which is likely related to the oxidative damage in the midgut caused by glyphosate exposure and is consistent with previously reported results (Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Lipase can decompose triglycerides into fatty acids and glycerol. In this study, we found that the activity of lipase was increased at 24 h, which is likely related to the oxidative damage in the midgut caused by glyphosate exposure and is consistent with previously reported results (Wang et al, 2019). We found that glyphosate caused significant damage to the midgut of silkworms, including thinner midgut basal layer, sparse microvilli, shedding of intestinal wall cells, blurred cytoplasmic membrane boundaries, and visible cell vacuoles (Figure 3).…”
Section: T a B L Esupporting
confidence: 92%
“…In addition, the gene encoding lipase 1, LOC101735952 , was transcriptionally upregulated, which was 1.76‐fold of the control group. Studies have shown that the lipase activity in silkworm was significantly increased after 24 h of glyphosate exposure, and then significantly decreased after 48 h (Feng et al, 2022); moreover, it has been shown that acetamiprid exposure led to a transient increase in lipase activity in silkworm, which might be related to inflammation (Wang et al, 2019). These results were similar to our results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Previous studies have shown that long-term exposure to trace amounts of pesticides, such as acetamiprid, phoxim and chlorantraniliprole, can lead to growth retardation, weight loss, disruption of molting and pupation, and reduced spinning ability in silkworms. 3,[6][7][8] On the other hand, few studies have focused on remedies for pesticide-poisoned silkworms. Thus, understanding the sublethal impacts of short-term pesticide exposure on silkworms can help to seek potential solutions to reduce the economic losses caused by pesticide poisoning.…”
mentioning
confidence: 99%
“…2 The toxicity of low-dose pesticides to silkworms has aroused concerns of researchers, and sublethal effects of some pesticides on silkworms have been partially investigated. [3][4][5] Previous studies have shown that long-term exposure to trace amounts of pesticides, such as acetamiprid, phoxim and chlorantraniliprole, can lead to growth retardation, weight loss, disruption of molting and pupation, and reduced spinning ability in silkworms. 3,[6][7][8] On the other hand, few studies have focused on remedies for pesticide-poisoned silkworms.…”
mentioning
confidence: 99%